Getting better at chronic care in remote communities: study protocol for a pragmatic cluster randomised controlled of community based management - Schmidt, Barbara (BioMed Central, 2012)
BACKGROUND: Prevalence and incidence of diabetes and other common comorbid conditions (hypertension, coronary heart disease, renal disease and chronic lung disease) are extremely high among Indigenous Australians. Recent measures to improve quality of preventive care in Indigenous community settings, while apparently successful at increasing screening and routine check-up rates, have shown only modest or little improvements in appropriate care such as the introduction of insulin and other scaled-up drug regimens in line with evidence-based guidelines, together with support for risk factor reduction. A new strategy is required to ensure high quality integrated family-centred care is available locally, with continuity and cultural safety, by community-based care coordinators with appropriate system supports. METHODS/DESIGN: The trial design is open parallel cluster randomised controlled trial. The objective of this pragmatic trial is to test the effectiveness of a model of health service delivery that facilitates integrated community-based, intensive chronic condition management, compared with usual care, in rural and remote Indigenous primary health care services in north Queensland. Participants are Indigenous adults (aged 18–65 years) with poorly controlled diabetes (HbA1c>=8.5) and at least one other chronic condition. The intervention is to employ an Indigenous Health Worker to case manage the care of a maximum caseload of 30 participants. The Indigenous Health Workers receive intensive clinical training initially, and throughout the study, to ensure they are competent to coordinate care for people with chronic conditions. The Indigenous Health Workers, supported by the local primary health care (PHC) team and an Indigenous Clinical Support Team, will manage care, including coordinating access to multidisciplinary team care based on best practice standards. Allocation by cluster to the intervention and control groups is by simple randomisation after participant enrolment. Participants in the control group will receive usual care, and will be wait-listed to receive a revised model of the intervention informed by the data analysis. The primary outcome is reduction in HbA1c measured at 18 months. Implementation fidelity will be monitored and a qualitative investigation (methods to be determined) will aim to identify elements of the model which may influence health outcomes for Indigenous people with chronic conditions. DISCUSSION: This pragmatic trial will test a culturally-sound family-centred model of care with supported case management by IHWs to improve outcomes for people with complex chronic care needs. This trial is now in the intervention phase. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ACTR12610000812099